PROSEDUR PEMERIKSAAN CT-SCAN KEPALA PEDIATRIC DI INSTALASI RADIOLOGI RSUD KABUPATEN TEMANGGUNG - Virzio Tri Pradana; Sofie Nornalita Dewi; Arnefia Mei Yusnida (Journal of Innovation Research and Knowledge, 2025)
Background: Head CT scans performed at the Pediatric Radiology Unit of Temanggung Regency Hospital use the adult head protocol (Head Helical). This differs from the theory that specific head protocols are required for each age group. The purpose of this study was to determine the pediatric head CT scan procedure at the Radiology Unit of Temanggung Regency Hospital, the rationale for using the adult head CT scan protocol for pediatric head CT scans, and the radiation protection measures implemented during pediatric head CT scans. Methods: This study employed a descriptive qualitative method with a case study approach. Data were collected through observation, interviews, documentation, and literature review at the Radiology Unit of Temanggung Regency Hospital. Subjects included three radiographers and one radiation protection officer, with the pediatric head CT scan procedure as the object of the study. Data were analyzed through observation, interviews, and documentation. Interview results were transcribed and then summarized using a categorization table. The summarized data were presented in narrative form and explained with a theoretical basis to draw conclusions. Results: Pediatric head CT scans performed at the Radiology Department of Temanggung District Hospital used the adult protocol (Head Helical) without modifications based on age classification. Parameters such as tube voltage (120 kV) and current (300 mAs) were the same for infants and children, resulting in CTDIvol (78.1 mGy) and DLP values exceeding the BAPETEN IDRL standard. Although diagnostic imaging results were considered good, the risk of high radiation exposure remains a concern. Several reasons for the lack of protocol adjustments for pediatric head CT scans include: habit, timeliness, culture, and prioritizing good image quality. Radiation protection for patients and caregivers was implemented according to standards, including the use of aprons and educational procedures. Conclusion: The procedure was largely in accordance with theory from a technical and protective perspective, but the use of the adult protocol without adjustments increases the risk of overdose in pediatric patients. Periodic evaluation and implementation of pediatric-specific protocols based on the ALARA principle are strongly recommended for pediatric patient safety